USE OF DATABASES IN RISK ASSESSMENT FOR THE OPERATION AND MAINTENANCE OF MEDICAL EQUIPMENT - Stefanov, Kiril; Yordanova, Marinela (E-Journal VFU, 2025)
This paper presents the design and application of a relational database system to support risk assessment in the operation and maintenance of medical equipment. The proposed system enables systematic registration of equipment, tracking of maintenance, repairs, calibration, and inspections, as well as recording of responsible personnel and vendors. By providing traceability, trend analysis, and real-time monitoring of failures, the database facilitates early detection of hazards, improves decision-making on equipment replacement, enhances staff training, and contributes to cost-effective budget planning.
Keywords: Risk Assessment; Medical Equipment; Database; Equipment Lifecycle; Maintenance and Repair; Safety